KEMAMPUAN SISWA MENYELESAIKAN SOAL HIGHER ORDER THINKING SKILLS (HOTS) PADA PEMBELAJARAN IPA DI KELAS V SD - Firly Istiqomah; Ayuningrum, Ayuningrum; Supriyanti, Yeti; Yuyu Yuhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
With the development of the current education curriculum, teachers and educators must use HOTS questions more in the learning and assessment process. Students do not just passively remember or understand information; these questions encourage them to apply, analyze, evaluate, and create based on the material they have learned It is anticipated that the intellectual capacities of students encompass not only extensive and profound analytical skills but also the capability to address emerging challenges in a continuously evolving world. This research delves into the competence of students to resolve questions categorized under HOTS at the C4, C5, and C6 levels, as outlined in Bloom’s taxonomy, utilizing a quantitative descriptive approach. Findings from this investigation reveal that fifth-grade students at UPT SDN Panyirapan demonstrate proficient problem-solving skills in science-related HOTS queries, achieving an average score of 71.55 across each HOTS level.